The Effect Of Earning Per Share (Eps), Price Earning Ratio (Per), And Company Size On Stock Prices In Food And Beverage Sub Sector Companies Listed On The Indonesia Stock Exchange 2016-2020 - Menik Istiningrum; Evaliati Amaniah (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
The research method used is quantitative. The analysis used is multiple linear regression analysis. The data used in this study is secondary data obtained from the Indonesia Stock Exchange (IDX) with a sampling technique using the purposive sampling method, and the number of samples obtained is 20 companies from 30 companies.The hypothesis testing used is multiple linear regression analysis using the SPSS program. Prior to multiple linear regression analysis, what needs to be done is the classical assumption test. Based on the data normality, multicollinearity test, heteroscedasticity test and autocorrelation test, there are no variables that deviate from the classical assumption test. The results of the F test are known that EPS, PER and company size have a positive and significant effect on stock prices in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) which means the hypothesis is accepted and the results of the t test are known that partially EPS has a positive and positive effect. significant on stock prices as evidenced by a significance value of 0.00 0.05, PER has a positive and insignificant effect as evidenced by a significance value of 0.492 0.05, company size has a negative and insignificant effect on stock prices as evidenced by a significance value of 0.104 0.05, the coefficient of determination (R²) is 0.382%, meaning that the independent variables together are able to explain the dependent variable of 38.2% while the remaining 61.8% is explained by other variables not included in this research model.